External Evaluation in Improving Learners’ Outcomes in Basic Schools: Challenges and Way Forward - Moses Adeleke Adeoye; Olaolu Paul Akinnubi (ASEAN Journal of Science and Engineering Education, 2024)
The paper examined the challenges and solutions to the eternal evaluation of learners' learning outcomes at public basic schools. Basic school is important for students’ improvement since it relates to students’ understanding for basic knowledge, including mathematics and science. Implementing external evaluation in Nigerian basic schools can be challenging due to a variety of factors. These may include limited resources, cultural barriers, and a lack of understanding of the purpose and value of evaluation. One way forward in addressing these challenges is to increase awareness and understanding of the importance of evaluation in improving learners' outcomes. This can be achieved through training and capacity building for stakeholders, including teachers, school administrators, and government officials. Ultimately, improving learners' outcomes in Nigerian basic schools requires a collaborative effort involving all stakeholders, including policymakers, educators, and communities. By working together and embracing new approaches and technologies, all learners have access to high-quality education and opportunities to promote continuous improvement and excellence in education.